Dawr al-ṣukūk al-murtabiṭah bi al-waqf al-naqdī fī taṭwīr mu'assasat al-ri‘āyah al-ṣiḥḥīyah bi Banten - Yasin, Yuli (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
This article aims to analyze the role of Cash Waqf Linked Sukuk (CWLS) in the development of healthcare services, particularly eye health, during the Covid-19 pandemic in Indonesia. The study adopts a descriptive qualitative approach, utilizing field research that involves analyzing social facts, expert opinions, and theoretical debates. The study findings indicate that the proceeds from CWLS, managed by the Indonesian Waqf Board (BWI) as the nāẓir (trustee), were used to purchase equipment for the retina and glaucoma center and provide patient transportation at Achmad Wardi Hospital. The utilization of CWLS proceeds significantly benefited 2,162 patients with retinal and glaucoma conditions, who faced challenges in accessing medical treatment and were at risk of blindness due to regional and social mobility restrictions during the pandemic. The model of utilizing CWLS proceeds for healthcare facility development at Achmad Wardi Hospital, implemented by BWI, can be replicated by other cash waqf trustees through collaboration with healthcare entities that cater to the community's needs.